CLINICOHISTOPATHOLOGICAL CHARACTERISTICS OF PROSTATE LESIONS AT RUMAH SAKIT PENDIDIKAN PROF. DR. CHAIRUDDIN PANUSUNAN LUBIS MEDAN, 2023-2024: KARAKTERISTIK KLINIKOHISTOPATOLOGI LESI PROSTAT DI RUMAH SAKIT PENDIDIKAN PROF. DR. CHAIRUDDIN PANUSUNAN LUBIS MEDAN, 2023–2024 - Lidya Imelda Laksmi; Causa Trisna Mariedina; Betty; Joko S Lukitoa; Arie Widiansyah Hasibuan (Ibnu Sina: Jurnal Kedokteran dan Kesehatan - Fakultas Kedokteran Universitas Islam Sumatera Utara, 2027)
Prostatic enlargement is a global health problem among older men, caused by non-neoplastic or neoplastic lesions and commonly presenting as lower urinary tract symptoms. Benign Prostatic Hyperplasia (BPH) is the leading non-neoplastic etiology, whereas Acinar Prostatic Carcinoma (APC) is the most common malignant neoplasm. High-Grade Prostatic Intraepithelial Neoplasia (HGPIN), a precursor lesion, and Atypical Small Acinar Proliferation (ASAP), a suspicious atypical acinar proliferation, are critical differential diagnoses and pitfalls influencing management and prognosis. Using total sampling, this retrospective cross-sectional study characterized clinicohistopathological features of prostatic lesions in patients undergoing prostate core needle biopsy and/or transurethral resection of the prostate at Rumah Sakit Pendidikan Prof. dr. Chairuddin Panusunan Lubis Medan, from January 2023 to June 2024. Histopathological evaluation used hematoxylin and eosin staining. Forty-three specimens were analyzed descriptively: 33 (76.74%) were BPH and 10 (23.26%) were APC; neither ASAP nor HGPIN was identified. Benign and malignant lesions occurred most frequently among patients aged 60–69 years; the youngest were aged 50–59 years. Ultrasonographic diagnoses agreed with histopathology in 83.33% of BPH cases and 66.67% of APC cases. BPH specimens predominantly showed papillary infolding and cystic atrophy, corpora amylacea as the principal intraluminal secretion, and squamous metaplasia as a distinctive finding. APC specimens predominantly showed tufting, cribriform, and micropapillary architectures; blue mucin and crystalloids as intraluminal secretions; and signet-ring cell morphology as a distinctive finding. Benign lesions showed papillary infolding and cystic atrophy, with intraluminal corpora amylacea. Malignant lesions showed tufting, cribriform and micropapillary patterns, with intraluminal blue mucin and crystalloids.